Engagement for Engagement’s Sake - Aukje van Rooden (Aesthetic Investigations, 2023)
The aim of this paper is to search for a new, contemporary, form of literary engagement by avoiding a return to the 20th century idea of literary engagement that presents literature either as autonomous and un-political or as explicitly committed to some political cause. Taking the Dutch poet laurate Lieke Marsman's debut novel Het tegenovergestelde van een mens (The opposite of a human being) as an exemplary case study, this paper stresses that the literature of the millennial generation explores a new and different form of engagement, a form that is consonant with our 21st century living conditions, that are more complex, fluid, and volatile than they have ever been.